(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article considers the main directions of research in the field of political linguistics. The last decades of the XX century and the beginning of the XXI century are marked by radical changes in the political structure of the world. The example is the collapse of two hostile camps (socialist and capitalist), and integration in Europe due to the globalization process. Politics, its institutions and processes do not exist regardless of the language and linguistic processes in the society. Political institution can not exist without communication. Thus, political texts and statements reflect the ideology, the system of natural-historical development of society and are a means of influencing public consciousness, i.e. they are characterized by the function of governing the society. Consequently, the study of political language was initiated by political problems, i.e. by the attempts of the thinking part of the society to free political communication from manipulation, as well as the needs of linguistic theory to determine the role of the linguistic phenomenon in political life (the use of euphemisms, metaphors).